Efektivitas Ekstrak Batang Arcangelisia flava Merr. sebagai Afrodisiaka pada Mencit Jantan dan Betina - Santi Nurul Kamilah; Eka Fitri Siti Andriyani; Dea Ananda Putri; Sri Astuti; Syalfinaf Manaf; Hari Marta Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aimed to analyze the effect of the stem extract of the yellow root plant (Arcangelisia flava Merr.) from Enggano Island on the introduction and locomotor activity of male and female mice (Mus musculus L.). The method used is an experiment with a completely randomized design. The treatment variations were extracted at a dose of 150 mg/kgBW, 200 mg/kgBW and 250 mg/kgBW, Neo Hormoviton capsules at a 200 mg/kgBW dose as a positive control, and without extract or strong drug as a negative control. The results showed that the administration of the extract caused an increase in the introduction activity, but the activity decreased with the increase in the dose of the given extract. Meanwhile, an increase in locomotor activity occurred at a dose of 250 mg/kgBW, while the doses of 150 mg/kgBW and 200 mg/kgBW tended to cause a decrease. Duncan's further test showed that a dose of 250 mg/kgBW increased locomotor activity which was more significant in female mice but not significantly in male mice. In conclusion, the extract at a dose of 250 mg/kgBW can increase locomotor activity, higher than Neo Hormoviton capsules at 200 mg/kgBW in both male and female mice. Keywords: Aphrodisiac, Sexual Activity, Arcangelisia flava, Fitness